Design of digital environments to enhance handicraft co-learning experiences - Supaporn Chai-Arayalert; Ketsaraporn Suttapong; Surin Chumkaew (Cogent Business & Management, 2023)
This research aimed to develop a digital platform that efficiently utilizes co-learning experiences between consumers and producers and to foster the preservation of local handicrafts in a manner that is both sustainable and economically feasible. This platform combines the co-design method with Kolb's experiential learning model, with a specific emphasis on improving the self-design process of local handicrafts. The research and development (R&D) methodology involves a systematic approach to addressing stakeholder needs through feedback and iteration, ensuring the final system is tailored to their specific objectives. The evaluation of the platform indicates that participants were highly satisfied with its performance. The platform facilitates extensive opportunities for collaborative participation and the exchange of knowledge, allowing participants to gain a comprehensive understanding of the processes involved in handicraft design. This research contributes to combining a virtual environment with a co-design process and Kolb's experiential learning model. The research contributes to the possibility of expansion of local crafts and the preservation of traditional workmanship, which can be achieved through collaboration between local artisans and global consumers. Encouraging consumer involvement in collaborating with the handicraft community has the potential to provide new product designs for markets, thereby boosting economies.
Keywords: 650; co-learning approach; digital platform; experiential learning; handicraft; self-design approach